Myth Analysis of Umpasa Batak Toba: Roland Barthes Semiotics Study - Tresia Anggraini Malau (Lakhomi Journal Scientific Journal of Culture, 2022)
This study aims to analyze the terms and describe the lexical meaning contained in the term marriage of the Toba Batak tribe. The author uses a qualitative research method with a descriptive approach. The results of the analysis of myths in the umpasa above, it can be concluded that it is an oral literary work that comes from reason or the thoughts of previous ancestors. That is why the Toba Batak umpasa cannot be separated from the myths of the past. The myths that are still very developed in society, especially in umpasa, are a). Hula-hula has the highest authority in the Toba Batak culture. This myth applies depending on the context. Where realistically hula-hula is basically the same as other positions. There is no dominant position. All are equal before the law. b). Sahala is identified with magic, security, wisdom, and harmony. Where if judging in reality sahala is a spirit that has no control and supernatural powers. c). Padan is associated as a sacred covenant. The assumption that Padan is sacred because it is believed will bring disaster if it is not kept. d). Children are a symbol of wealth. The Toba Batak people fully believe that having many children will also have a lot of sustenance. This belief is no stranger to the ears. Those who do not have children will be considered poor by the local community, because no one will continue the lineage